2004
DOI: 10.1074/jbc.m309505200
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Respiratory Complexes I, III, and IV into NADH Oxidase Supercomplex Stabilizes Complex I in Paracoccus denitrificans

Abstract: J. Biol. Chem. 260, 2458 -2467). However, these assemblies did not comprise complex I (NADH:ubiquinone oxidoreductase). Using the mild detergent digitonin for solubilization of Paracoccus denitrificans membranes we could isolate NADH oxidase, assembled from complexes I, III, and IV in a 1:4:4 stoichiometry. This is the first chromatographic isolation of a complete "respirasome." Inactivation of the gene for tightly bound cytochrome c 552 did not prevent formation of this supercomplex, indicating that this elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
172
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(188 citation statements)
references
References 50 publications
14
172
1
1
Order By: Relevance
“…Rather, the current results are in line with a growing body of work that now suggests that some mitochondrial electron-transfer complexes specifically interact to form supermolecular structures called supercomplexes in organisms ranging from the yeast Saccharomyces cerevisiae (35,36), beef (19,29,35,37), and plants (38)(39)(40)(41)(42). Similar supermolecular structures have also been described for the respiratory chains of bacteria (43)(44)(45)(46)(47). The roles that have been attributed to respiratory supercomplexes are substrate-channeling, catalytic enhancement, sequestration of reactive intermediates (35), stabilization of protein complexes (48), increasing the capacity of the inner mitochondrial membrane for protein insertion (36), and generating mitochondrial cristae morphology (49).…”
Section: Stepr Studies Of Spin-labeled Cytochrome Caa 3 Embedded In Psupporting
confidence: 71%
“…Rather, the current results are in line with a growing body of work that now suggests that some mitochondrial electron-transfer complexes specifically interact to form supermolecular structures called supercomplexes in organisms ranging from the yeast Saccharomyces cerevisiae (35,36), beef (19,29,35,37), and plants (38)(39)(40)(41)(42). Similar supermolecular structures have also been described for the respiratory chains of bacteria (43)(44)(45)(46)(47). The roles that have been attributed to respiratory supercomplexes are substrate-channeling, catalytic enhancement, sequestration of reactive intermediates (35), stabilization of protein complexes (48), increasing the capacity of the inner mitochondrial membrane for protein insertion (36), and generating mitochondrial cristae morphology (49).…”
Section: Stepr Studies Of Spin-labeled Cytochrome Caa 3 Embedded In Psupporting
confidence: 71%
“…Well characterized preparations of intact bacterial complex I have so far been obtained from E. coli (32,33), Aquifex aeolicus (34), and recently T. thermophilus (15). The P. denitrificans enzyme was previously isolated only either as a subcomplex (22) or in low yields as part of a supercomplex with respiratory complexes III and IV (35).…”
Section: Methodsmentioning
confidence: 99%
“…strain 7 has a terminal oxygen reductase supercomplex resulting from the functional fusion of complexes III and IV, containing cytochromes of the b and a types, and a Rieske-type ironesulfur protein [17,18]. A mitochondrial-like respirasome was identified in Paraccocus denitrificans [19] and supramolecular associations of complexes III and IV were detected in P. denitrificans [19,20], Corynebacterium glutamicum [21], and Bacillus PS3 [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been suggested that since it contains a detergent stable complex I and is devoid of complex III, such supramolecular organization is not necessary [19]. Nevertheless, co-localization of oxidative phosphorylation complexes has been suggested [30].…”
Section: Introductionmentioning
confidence: 99%